COPURE D2 MODULES - Gupta K.; Gupta S.; Gupta A.J. (My University, 2025)
This paper presents and investigate the concept of copure D2 modules, which serve as a generalization of D2 modules and the dual notion of copure C2 modules [8]. A module N is considered to be copure D2 if a quotient module determined by a copure submodule of N, is isomorphic to a summand of N, then that copure submodule is also a summand of N. In our discussion, we explore summands and direct sums of copure D2 modules and give new characterizations of semi-simple rings with respect to relative copure D2 modules. Also, we find connections among copure D2 modules, copure-Rickart modules, and endoregular modules. © Palestine Polytechnic University-PPU 2024.